Peningkatan Kemandirian Belajar melalui Layanan Bimbingan Kelompok - Elly Agustin Fitriana; Rahmat Mulyono (Syntax Corporation, 2023)
An attitude of independence can be shown by the ability to solve problems faced with behavior. With changes in behavior, students also have an increase in thinking, assuming that learning must be able to be independent without relying on help from others continuously and also do not depend on learning from teachers alone, but learning can also be from print, electronic and natural media. This type of research is a classroom action research with the number of research subjects is 32 children with the aim of research to find out group guidance services carried out by Guidance Counseling teachers at Mts Negeri 9 Gunungkidul. To find out the independence of student learning at MTs Negeri 9 Gunungkidul. To find out the results of Learning Independence through Group guidance services in grade 8 C MTs Negeri 9 Gunungkidul Yogyakarta. The results of the study increased children's learning independence in the second cycle in the first group by 22.1%. With an average score of 82.05, this means that children's independence is very good, where 5 children score between 70-80 including the medium category and 6 children above 80 who are included in the high learning independence category. The increase in children's learning independence in the second cycle in the second group was 25.1%. With an average score of 85.45, this means that children's independence is very good, where 4 children score between 70-80 including the medium category and 7 children above 80 who are included in the high learning independence category. The increase in children's learning independence in the second cycle in the third group was 21.7%. With an average score of 88, this means that children's independence is very good, where 10 children have been above the value of 80 which is included in the category of high learning independence.